Treatment of hepatic venous system hemorrhage and carbon dioxide gas embolization during laparoscopic hepatectomy via hepatic vein approach - Qu, Zhen; Wu, Ke-jia; Feng, Jia-wei; Shi, Ding-sen; Chen, Yu-xiang; Sun, Dong-lin; Duan, Yun-Fei; Chen, Jing; He, Xiao-zhou (Frontiers in Oncology, 2023)
With the improvement of laparoscopic surgery, the feasibility and safety of laparoscopic hepatectomy have been affirmed, but intraoperative hepatic venous system hemorrhage and carbon dioxide gas embolism are the difficulties in laparoscopic hepatectomy. The incidence of preoperative hemorrhage and carbon dioxide gas embolism could be reduced through preoperative imaging evaluation, reasonable liver blood flow blocking method, appropriate liver-breaking device, controlled low-center venous pressure technology, and fine-precision precision operation. In the case of blood vessel rupture bleeding in the liver vein system, after controlling and reducing bleeding, confirm the type and severity of vascular damage in the liver and venous system, take appropriate measures to stop the bleeding quickly and effectively, and, if necessary, transfer the abdominal treatment in time. In addition, to strengthen the understanding, prevention and emergency treatment of severe CO2 gas embolism in laparoscopic hepatectomy is also the key to the success of surgery.